The Effect of Educational Punishment on the Learning Motivation of Fifth-Grade Students at SDN 1 Selebung Ketangga - Moh. Irwan Hadi (LP2M STIT Palapa Nusantara, 2023)
Classroom discipline strategies are essential not only for correcting student behavior but also for supporting learning motivation in a proportional and educational manner. This study aims to analyze the effect of punishment on the learning motivation of fifth-grade students at SDN 1 Selebung Ketangga in the 2020/2021 academic year. This study employed a quantitative approach with an ex post facto design. The sample consisted of fifth-grade students selected through total sampling in the class under study. Data were collected through questionnaires, observation, and documentation and analyzed using simple linear regression with SPSS 22. The results indicate that punishment has a positive and significant effect on students’ learning motivation, as shown by a regression coefficient of 2.974 and a significance value of 0.006 (< 0.05). The model output also shows an R Square value of 1.000, indicating a very high predictive level in the available data and therefore requiring careful interpretation in the context of educational behavioral research. These findings suggest that educational, proportional, and nonphysical punishment accompanied by pedagogical explanation can function as behavioral feedback that supports students’ learning engagement. This study concludes that constructive classroom discipline plays an important role in maintaining elementary school students’ learning motivation when implemented ethically and proportionally. Theoretically, this study contributes to the literature on classroom management and learning motivation, while practically, it highlights the importance of discipline strategies that respect students’ psychological safety and promote positive learning behavior.